Enhancement of oxidative stability of soybean oil via nano-emulsification of eggplant peel extract: Process development and application. (15th February 2023) - Sharma, Simran; Chakkaravarthi, S.; Bhattacharya, Bhaswati
Highlights: Eggplant peel extract (EPE) nanoemulsion was formulated and optimized. Controlled release of EPE antioxidants was achieved through nanoemulsions. EPE nanoemulsion enhanced the oxidative stability of pure refined soybean oil. Oxidative stability of EPE nanoemulsion was comparable to commercial soybean oil. Abstract: To extend the oxidative stability of soybean oil with encapsulated natural antioxidants, eggplant peel-based water-in-oil (W/O) nanoemulsions were formulated. The nanoemulsions were developed with eggplant peel extract (1000–9000 ppm) and CR-310 emulsifier (8–10 %) via ultrasonication. Seven W/O nanoemulsion formulations exhibited high sedimentation stability (sedimentation index > 92.58 %), a mean droplet diameter < 100 nm and low polydispersity index (<0.25) during 30 days storage. These nanoemulsions achieved controlled release of polyphenols. The low conjugated diene and p-anisidine value (Schaal oven parameters) of the nanoemulsions compared to pure soybean oil and commercial soybean oil suggested that these W/O nanoemulsions restricted oxidation better than these oils. Moreover, they could control the oxidation of soybean oil for approximately 10–15 days under accelerated storage conditions. Further, the induction period in Rancimat also indicated that the nanoemulsions possessed higher oxidative stability compared to pure soybean oil while three nanoemulsions even exhibited higher induction period than commercial soybean oil.